Peranan Hakim Dalam Menetapkan Akta Perdamaian Menurut Hukum Acara Perdata - Rahardianti, Anak Agung Istri Mas; Rai Asmara Putra, Dewa Nyoman (Kertha Wicara : Journal Ilmu Hukum; Vol 10 No 1 (2020), 2020)
The purpose of this study is to determine the role of judges in determining peace deeds in civil court proceedings and the legal strength of peace deeds established by judges from the mediation process in civil disputes. The research method used in this research is a normative juridical legal research method through a statutory approach and a conceptual approach that is sourced from primary legal materials and is analyzed descriptively where it is done by describing realistically about a legal situation, and using qualitative analysis techniques by writing in a descriptive manner. narration which then contains the conclusion. From the results of this research, it is known that: (1) According to Article 130 HIR, the judge is obliged to reconcile the parties, including peace in court where the judge will make a peace deed which is an agreement made by two or more persons before the competent institution, which in the context of This is the judge as an authorized official, whose level is requested in the trial and is binding. (2) A peace agreement does not have legal force that provides legal certainty for the disputing parties, but a peace agreement will only have binding legal force when it has become a peace deed and to become a peace deed, a peace agreement or agreement must obtain strength from the assembly. judge as the competent authority. If the peace agreement has not been in the form of a deed then it is not strong enough, because the agreement is only limited to an agreement between the two parties, without any supervision by the competent institution. Keywords: Judges, Peace Deed, Civil Procedure Law